Изучение мотивации пациентов к отбеливанию твердых тканей зубов (LLC "Endo Press", 2020)
Psychological testing and diagnostic of 108 persons with different types of discolored teeth were conducted as well as with tooth discoloration after endodontic therapy. Patients motivation singularities analysis for patients which have chosen different type of hard tooth tissues whitening the following conclusions can be done. For in-office bleaching patients motivation of achievement predominates over motivation of approval and vice-versa for at-home bleaching patients motivation of approval predominates over motivation of achievement.